A photoswitchable Zn (II) selective spiropyran-based sensor - SOLDI, LAURA; GIORDANI, SILVIA; NATALI, MANUEL (My University, 2010)
A spiropyran-based fluorescent and photoregenerable receptor that is selective towards zinc(II) ions over a series of biologically and environmentally relevant cations has been designed and synthesized. The complex formation gives rise to color changes that are visible to the naked eye and reversible upon visible light irradiation. 1H-NMR studies confirm that the closed form is converted to the open trans-merocyanine complex upon addition of zinc ions.
PUBLISHED
Keywords: Biochemistry; Nanoscience & Materials